Optimal multi-criteria selection of hybrid energy systems for off-grid electrification - Ocon, Joey D. (Animo Repository, 2018)
Energy poverty or lack of access to electricity is still a pressing development challenge worldwide particularly in archipelagic countries like the Philippines and Indonesia. As rural electrification in these remote areas through on-grid extension becomes costly, these communities typically resort to diesel-powered off-grid generators, characterized by high operating costs, unstable supply and price of fuel, and environmental issues. The deployment of clean energy alternatives is clearly needed, but these must be selected systematically using multiple but possibly conflicting criteria. Currently, the decision on which technology to use is derived based on the levelized cost of electricity primarily. In this illustrative case study, a novel multi-criteria decision-making methodology is proposed for the selection of the most appropriate energy system for the off-grid electrification of Marinduque Island. Eight technology combination options were evaluated using six criteria covering socioeconomic, environmental, and technical aspects. Fuzzy AHP was used to derive weights of the criteria while addressing ambiguity and subjectivity of decision-makers. Performances of the technology options across different criteria were determined quantitatively via techno-economic simulations, or qualitatively via domain expert estimates. Grey Relational Analysis (GRA) was then used to aggregate the entire range of performance attributes of each alternative into a single score. Results indicate that system reliability and social acceptability are the most important criteria in selecting hybrid energy systems for off-grid electrification. Among the eight alternatives, the fuel saver (diesel-solar PV hybrid) and diesel-solar PV-Li-ion hybrid systems yield the highest performance scores. The prioritization was mainly affected by system reliability and social acceptability, indicating that decision making for the attainment of sustainable island energy supply should not be limited to technical and economic considerations only. This is consistent with the current worldwide trend of implementing the diesel-solar PV-Li-ion hybrid systems in off-grid areas, thus, validating the applicability of the facile methodology developed in this work. © 2018, AIDIC Servizi S.r.l.